PERAN SERTA MASYARAKAT DALAM TATA KELOLA SUMBER DAYA AIR DI KOTA MATARAM DAN KABUPATEN LOMBOK BARAT, NUSA TENGGARA BARAT (Kajian Berbasis Lingkungan dalam pengelolaan SDA) - Richardus Indra Gunawan, S.TP., M.Si Richardus Indra Gunawan, S.TP., M.Si (AGRONOMIKA, 2016)
Governance in water resources become the importance topic that concerned in today. This is based on the restricted role of the community. The actor that plays in the role is still from the government which also becomes regulator as well as executor. This research aim to gathering the information what is the best model that fit with the three party scheme (government, community, and business). The research held in Mataram City and West Lombok, West Nusa Tenggara by using purposive sampling with focus group discussion for two kinds of respondents, there are PDAM subscribers and non PDAM subscribers. From the research can be collected information that the higher participation from the community in water resources governance will impact to the guarantee of water supply to the wider community.